The neverending story II [videorecording (Blu-Ray)] : the next chapter - Howard, Karin; Brandis, Jonathan, 1976-2003; Morrison, Kenny; Shipp, John Wesley; Burt, Clarissa; Johnes, Alexandra; Umbach, Martin; Folk, Robert; Moroder, Giorgio; Connell, David, 1958-; Ende, Michael; Geissler, Dieter, 1939- ([Publisher not identified], 2014)
Based on Michael Ende's classic children'sbook, this sequel finds the young her, Bastian, encountering new adventures in the magical world of fantasia. In the sequel to the 1984 film, our young hero, again bored with the real world, returns to his storybook's magical land of Fantasia and attempts to slay the evils that threaten the extinction of goodness. There he finds a special brand of courage within himself, a reminder of the eternal, optimistic child within us all.